Predictors of Pathologic Complete Response Following Neoadjuvant Chemoradiotherapy for Rectal Cancer - Al-Sukhni, Eisar (Ann Surg Oncol, 2015)
BACKGROUND: Some patients with rectal cancer who receive neoadjuvant chemoradiotherapy (nCRT) achieve a pathologic complete response (pCR) and may be eligible for less radical surgery or non-operative management. The aim of this study was to identify variables that predict pCR after nCRT for rectal cancer and to examine the impact of pCR on postoperative complications. METHODS: A retrospective review was performed of the NCDB from 2006 to 2011. Patients with rectal cancer who received nCRT followed by radical resection were included in this study. Multivariable analysis of the association between clinicopathologic characteristics and pCR was performed, and propensity-adjusted analysis was used to identify differences in postoperative morbidity between pCR and non-pCR patients. RESULTS: A total of 23,747 patients were included in the study. Factors associated with pCR included lower tumor grade, lower clinical T and N stage, higher radiation dose, and delaying surgery by more than 6–8 weeks after the end of radiation, while lack of health insurance was linked with a lower likelihood of pCR. Complete response was not associated with an increased risk of major postoperative complications. CONCLUSIONS: Several clinical, pathologic, and treatment variables can help to predict which patients are most likely to have pCR after nCRT for rectal cancer. Awareness of these variables can be valuable in counseling patients regarding prognosis and treatment options.